Geochemical analysis of sediments from a semi-enclosed bay (Dongshan Bay, southeast China) to determine the anthropogenic impact and source. (May 2017) - Xu, Yonghang; Sun, Qinqin; Ye, Xiang; Yin, Xijie; Li, Dongyi; Wang, Liang; Wang, Aijun; Li, Yunhai
Abstract: The geochemical compositions of sediments in the Dongshan Bay, a semi-enclosed bay on the southeast coast of China, were obtained to identify pollutant sources and evaluate the anthropogenic impacts over the last 100 years. The results indicated that the metal flux had been increasing since the 1980s. Enrichment factor values (Pb, Zn and Cu) suggested only slight enrichment. The proportion of anthropogenic Pb changed from 9% to 15% during 2000–2014. Coal combustion might be an important contamination source in the Dongshan Bay. The historical variation in the metal flux reflected the economic development and urbanization in the Zhangjiang drainage area in the past 30 years. According to the Landsat satellite remote sensing data, the urbanization area expanded approximately three times from 1995 to 2010. The δ 13 C values (−21‰ to −23‰) of the organic matter (OM) in the sediments indicated that the OM was primarily sourced from aquatic, terrigenous and marsh C3 plants. Nitrogen was mainly derived from aquatic plants and terrigenous erosion before the 1980s. However, the total organic carbon (TOC) contents, total nitrogen (TN) contents and δ 15 N had been increasing since the 1980s, which suggested that the sources of nitrogen were soil erosion, fertilizer and sewage. In addition, the TOC and TN fluxes in the Dongshan Bay had significantly increased since the 1980s, which reflected the use of N fertilizer. However, the TOC and TN fluxes significantly decreased in the past decade because environmental awareness increased and environmental protection policies were implemented. Graphical abstract: Highlights: Heavy metals, Pb isotopes and biogenic elements from a semi-enclosed bay were analysed. EFs and Pb isotopes indicated minor pollution in the past 30 years. OM was primarily derived from aquatic plants, terrigenous erosion, fertilizers and sewage. The TOC and TN fluxes had increased since the 1980s, reflecting the use of N fertilizer.